Pengaruh Kompensasi Non-Finansial dan Kesejahteraan Guru terhadap Motivasi Mengajar Guru di Smp Islam Manbaul Ulum Jamanis - Isna Zulfa Amanillah; Sri Sudiarti (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2026)
This empirical study is driven by the identified issue of suboptimal teaching motivation among educators at SMP Islam Manba'ul Ulum Jamanis, as evidenced by a preliminary survey score of 1.9. This unfavorable condition is presumably tied to less-than-ideal non-monetary appreciation and insufficient teacher welfare within the institution. This research is designed to explore and analyze both the isolated and simultaneous impacts of Non-Financial Compensation and Teacher Welfare on Teacher Teaching Motivation. Employing a quantitative design, this study adopts descriptive and verificative approaches. The research encompasses the entire teaching staff, totaling 30 educators, utilizing a saturated sampling (census) technique to achieve comprehensive data representation. Data processing was conducted via multiple linear regression analysis facilitated by SPSS 26 software. The empirical findings reveal that, both partially and simultaneously, Non-Financial Compensation and Teacher Welfare exert a positive and statistically significant influence on Teacher Teaching Motivation. Collectively, these two independent variables explain 41.4% of the variance in teaching motivation, while the remaining 58.6% is attributable to external determinants outside the scope of this analytical model.